Intra coronary freshly isolated bone marrow cells transplantation improve cardiac function in patients with ischemic heart disease - Bozdag-Turan, Ilkay (BioMed Central, 2012)
BACKGROUND: Autologous bone marrow cell transplantation (BMCs-Tx) is a promising novel option for treatment of cardiovascular disease. In this study we analyzed whether intracoronary autologous freshly isolated BMCs-Tx have beneficial effects on cardiac function in patients with ischemic heart disease (IHD). RESULTS: In this prospective nonrandomized study we treated 12 patients with IHD by freshly isolated BMCs-Tx by use of point of care system and compared them with a representative 12 control group without cell therapy. Global ejection fraction (EF) and infarct size area were determined by left ventriculography. Intracoronary transplantation of autologous freshly isolated BMCs led to a significant reduction of infarct size (p < 0.001) and an increase of global EF (p = 0.003) as well as infarct wall movement velocity (p < 0.001) after 6 months follow-up compared to control group. In control group there were no significant differences of global EF, infarct size and infarct wall movement velocity between baseline and 6 months after coronary angiography. Furthermore, we found significant decrease in New York Heart Association (NYHA) as well as significant decrease of B-type natriuretic peptide (BNP) level 6 months after intracoronary cell therapy (p < 0.001), whereas there were no significant differences in control group 6 months after coronary angiography. CONCLUSIONS: These results demonstrate that intracoronary transplantation of autologous freshly isolated BMCs by use of point of care system is safe and may lead to improvement of cardiac function in patients with IHD. TRIAL REGISTRATION: Registration number: ISRCTN54510226